Occurrence of Legionella spp. in Clinical and Environmental Samples in Babylon Province - Owayid Adday Azhar Althahab, Abdulrasool; Saadi Alwash, Mourouge (International Journal of Psychosocial Rehabilitation, 2020)
This study was designed to determine the occurrence of Legionella spp. recovered from clinical (sputum and dental wash) and environmental (hospital and domestic water system, air conditioner, showers, and tap water) samples using standard biochemical tests. All samples were diluted (1:10) in a KCl–HCl solution (pH 2.0); this was mixed and incubated at room temperature for 45 min to avoid the growth of other undesired bacteria and to facilitate the better isolation of Legionella spp. Supernatant was discarded, and the sediment was transferred and cultured on buffered yeast extract (BCYE) agar culture medium. The culture media were incubated at 37 °C for 36 hours without CO₂ and 5 days in 2.5 % CO₂.. The degree of the occurrence of Legionella pneumophila in clinical remains high (18.5%) in comparison with environmental samples (12.7%).